Serum Protein Electrophoresis May Be Used as a Screening Tool for Antibody Deficiency in Children and Adolescents - Piza, Cristina Frias Sartorelli de Toledo; Aranda, Carolina Sanchez; Solé, Dirceu; Jolles, Stephen; Condino-Neto, Antonio (Frontiers in Immunology, 2021)
Background: Patients with antibody deficiency may experience exceptionally long diagnoses delays, increasing the risk of life-threatening infections, end-organ damage, mortality, and health costs. Objective: This study aimed to analyze serum protein electrophoresis and verify the correlation between calculated globulin (CG, total protein minus albumin levels) or electrophoretically determined serum gamma globulin fraction (Gamma) with IgG levels in children and adolescents under 18 years old (yo). Methods: We analyzed serum protein electrophoresis (GC or Gamma) and IgG levels from 1215 children and adolescents under 18 yo, classified into 5 age groups. We verified the correlation between CG or Gamma with serum IgG levels. Results: Serum IgG levels varied according to age groups (from 4.3 ± 2.3 g/l in children under 6 months old to 11.4 ± 3.2 g/l in adolescents in the 10-<18 yo group). CG sensitivity and specificity for all patients were 93.1% and 81.8%, respectively, and varied according to age group. Gamma sensitivity and specificity for all patients were 100% and 87.8%, respectively, and varied according to age group as well. We found serum IgG levels below the age reference level in 29 patients (2.4% of the cases) using CG or Gamma levels. Conclusion: Both CG and Gamma levels may be of utility as a screening tool for earlier diagnosis of antibody deficiency in children and adolescents under 18 yo,